Gestão do território: multifuncionalidade rural e turismo como estratégias para o desenvolvimento rural - Maia, Adriano Corrêa [UNESP]; Ferreira, Darlene Aparecida de Oliveira [UNESP] (My University, 2011)
The article analyses the possibilities of Geography concepts and categories to contribute to the notion of rural multi-functionality. It points out indications in the social-economic concepts development of small proprieties, emphasizing their relation to tourism. Thereby, the text aims at presenting theoretical and methodological elements of management of the geographic space, with the purpose of enabling the creation of tools which propitiate a support in the constructions of strategies of rural and local management.

A partir da discussão da noção de multifuncionalidade rural, o artigo aborda as possibilidades de contribuição da ciência geográfica, com seus conceitos e categorias, em apontar indicativos nas discussões sobre o desenvolvimento econômico-social de pequenas propriedades, enfatizando a sua relação com o turismo. Para isso, o texto objetiva apresentar elementos teóricos e metodológicos da gestão do espaço geográfico, com a intenção de viabilizar a criação de ferramentas que possibilitem um suporte na construção de estratégias de planejamento local e rural.
Territory management: multi-functionality and tourism as strategies for rural development
Keywords: Rural tourism; Territory management; Multi-functionality; Agricultura familiar; Multifuncionalidade; Políticas públicas; Desenvolvimento rural